Application of Chemical Techniques in the Manufacture of Some Industrial Dental Materials - Hamed Ibrahim Mohammed1, Aara Ali Hadi1, Hassanain jwad abid al Hussein1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
This method of manufacturing Separating Medium was used in the field of chemical polymerization, in which a semi-gelatinous liquid was placed on the dental kits to prevent the adhesion of the gypsum material to the dermis made of hot processed polymer. After the experiments on the plant seeds, specifically the flax plant, the final extraction of the substance has been reached. It has given all the desired good specifications that are used in the field of dentistry. It is known that this material is a polar compound was diluted with distilled water after preparation. It is worth mentioning that 10% of the industrial pigments have been added to give them the red or pink color as these colors are desirable and common in the commercial markets as well as It is recommended for the dental products manufacturers, as well as 10% of the original alcohol and 1% of formalin to prevent the growth of bacteria and other types of microorganisms that cause rotting and decomposition of the manufactured material.